2012
DOI: 10.3342/ceo.2012.5.1.39
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Population-based Study of Total Nasal Resistance in Korean Subjects

Abstract: ObjectivesRhinomanometry is a widely accepted method for objective assessment of nasal patency. However, few studies have reported the values of otherwise healthy population for nasal resistance in East Asians. The purpose of this study was to measure normal total nasal resistance (TNR) values in a large sample of Korean adults and to reveal parameters contributing to TNR values.MethodsSubjects were enrolled from a cohort of the Korean Genome and Epidemiology Study. They were evaluated by anthropometry, questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Our finding for the mean total nasal resistance in Chinese subjects measured using a pressure of 150 Pa was lower than the mean value of 0.32 Pa/cm 3 /sec (95% CI, 0.10 to 0.54 Pa/cm 3 /sec) noted by Canakcloglu et al . for a cohort of 2216 white subjects; and higher than a value of 0.22 Pa/cm 3 /sec (96% CI, 0.04 to 0.40 Pa/cm 3 /sec) noted by Kim et al . for a cohort of 2538 Korean subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…Our finding for the mean total nasal resistance in Chinese subjects measured using a pressure of 150 Pa was lower than the mean value of 0.32 Pa/cm 3 /sec (95% CI, 0.10 to 0.54 Pa/cm 3 /sec) noted by Canakcloglu et al . for a cohort of 2216 white subjects; and higher than a value of 0.22 Pa/cm 3 /sec (96% CI, 0.04 to 0.40 Pa/cm 3 /sec) noted by Kim et al . for a cohort of 2538 Korean subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…17,[28][29][30] Among changes in size and shape of the respiratory and vocal tracts, laryngeal descent, associated with hyoideal descent, is greater in males, resulting in relatively longer airways. 31,32 No gender differences in nasal resistance have been found for children, 13,14,16 while Kim et al 23 reported lower resistance for females and also a decrease in resistance with age among adults. Although upper airway resistance decreases with age in children, Saito and Nishihata 14 found a temporary increase between ages 13 and 14, paralleling our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Kobayashi et al 16,17 found a tendency that resistance decreased with increasing height in schoolchildren but the correlations between resistance and weight, height, body surface or body mass index (BMI 5 Weight (kg)/[Height (m)] 2 ) were weak. Kim et al 23 reported that in the adult population, lower body weight was related to increasing total nasal resistance in women but not in men. In contrast, Saito and Nishihata 14 did not find a significant correlation between nasal resistance and height or weight in 5-17-year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…Even though cigarette smoking did not reach statistical significance, it is also known to be associated with increased total nasal resistance, and Russo-Magno et al [24] and Kim et al [26] reported an association between cigarette smoking and noncompliance. In this study, smoking only had a trend for low average daily CPAP use without statistical significance.…”
Section: Discussionmentioning
confidence: 99%